Electro-optical Switching of a Topological Polariton Laser - Gagel, Philipp; Harder, Tristan H.; Betzold, Simon; Egorov, Oleg A.; Beierlein, Johannes; Suchomel, Holger; Emmerling, Monika; Wolf, Adriana; Peschel, Ulf; Hoefling, Sven; Schneider, Christian; Klembt, Sebastian (ACS Photonics, 2022)
Implementing concepts of topological protection in photonics has proved to be an exciting new degree of freedom for the realization of photonic devices. In this work, we are using arrays of coupled microresonators to realize exciton-polariton lasing from a topological domain boundary defect in an orbital Su-Schrieffer-Heeger geometry. By implementing adequate doping levels and the application of a bias voltage, we show that we can use the quantum confined Stark effect to control the condensation of polaritons in the topological mode. Specifically, we demonstrate that we can influence the polariton condensation behavior such that we can switch lasing from the topological defect to a trivial mode. We believe that successfully triggering the crossover from the topologically protected to the trivial regime of a nonlinear Bosonic condensate via eletro-optical methods paves the way toward ultrafast, topologically protected photonic switches, possibly down to the single photon level. Furthermore, we anticipate that a periodic electro-optical modulation can establish a new degree of freedom to tailor the optical properties of topologically protected polariton condensates.
CRIS-Team Scopus Importer:2023-04-20
Keywords: doped microcavity; electrical manipulation; exciton-polariton; polariton condensation; topological lasing; zigzag chain